ESR-DATING OF THE ARCTIC SEDIMENT CORE PS1535 DOSE-RESPONSE AND THERMAL BEHAVIOUR OF THE CO2--SIGNAL IN FORAMINIFERA - Hoffmann D.; Woda C.; Strobl C.; Mangini A. (My University, 2001)
ESR-spectra of foraminifera in arctic sediment cores display the CO2--signal (g=2.0006). Research on the thermal behaviour of the CO2--signal shows that both natural and artificial irradiation generates a precursor and a thermal unstable component of the CO2--signal. The precursor can be transfered to the stable radical, and unstable radicals can be removed by heating. The signal-change by heating depends on the irradiation dose. Because of the varying response on thermal treatment, the dose-response curves show systematic differences depending on the applied procedure (single- or multi-aliquot method with or without heating). A model for the description of the CO2--signal-change is presented. The combination of two exponential saturation functions seems to be an adequate analytical description of the dose-response curve of the CO2--signal in foraminifera. Due to the limited thermal stability this signal can be used for dating foraminifera with ages up to about 190ka.
Keywords: ESR-dating; foraminifera